Graphene production by cracking - Bohm,S; Ingle,A; Bohm,M; Fenech,Salerno B; Wu,S; Torrisi,F (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2021)
n recent years, graphene has found its use in numerous industrial applications due to its unique properties. While its impermeable and conductive nature can replace currently used anticorrosive toxic pigments in coating systems, due to its large strength to weight ratio, graphene can be an important component as a next-generation additive for automotive, aerospace & construction applications. The current bottlenecks in using graphene & graphene oxide and other 2D materials are the availability of cost-effective, high-quality materials and their effective incorporation (functionalisation and dispersion)into the product matrices. On overcoming these factors, graphene may attract significant demands in terms of volume consumption. Graphene can be produced on industrial scales and cost-effective top-down routes such as chemical, electro chemical, and/or high-pressure mechanical exfoliation. Graphene depending on end applications can be chemically tuned and modified via functionalisation so that easy incorporation into product matrices is possible. This paper discusses different production methods and their impact on the quality of graphene produced in terms of energy input. Graphene with an average thickness below five layers were produced by both methods with varied defects. However, a higher yield of graphene with a lower number of layers was produced by the high-pressure exfoliation route.